Pedagogical Practices and Their Impact on Critical Thinking Skills in Indonesian Islamic Higher Education - Kholis, Nur (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2025)
This study examines the effectiveness of learning approaches used by State Islamic Higher Education Institutions (PTKIN) in promoting students' critical thinking skills. A mixed-method approach was employed, integrating survey, interview, and observation techniques to collect comprehensive data. Students reported struggling with academic text comprehension (M = 2.03, SD = 0.176) and evaluation (M = 2.41, SD = 0.614), while indicating moderate satisfaction with learning systems (M = 2.94, SD = 0.618), and providing neutral-to-positive evaluations of lecturer quality (M = 2.75, SD = 0.100). Drawing on Bloom’s Taxonomy, constructivist learning theories, and the distinction between superficial and deep learning, the analysis highlights the need for pedagogical reforms that integrate active learning, collaborative problem-solving, and inquiry-based instruction. By bridging the gap between traditional religious pedagogy and contemporary educational objectives, Islamic higher education institutions can better equip graduates to engage critically with religious texts and apply their knowledge to real-world challenges, fostering both intellectual and spiritual growth. These findings imply that adopting student-centered and inquiry-based pedagogies in Islamic higher education can significantly enhance students’ critical thinking skills and better prepare them for complex societal demands.